2012
DOI: 10.1016/j.visres.2012.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the time course and nature of attentional disengagement effects

Abstract: Visual features of fixated but irrelevant items contribute to both how long overt attention dwells at a location and to decisions regarding the location of subsequent attention shifts (Boot & Brockmole, 2010; Brockmole & Boot, 2009). Fixated but irrelevant search items that share the color of the search target delay the deployment of attention. Furthermore, eye movements are biased to distractors that share the color of the currently fixated item. We present a series of experiments that examined these effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 34 publications
4
30
1
Order By: Relevance
“…Compared with when the center object was any other color, saccades away from the center object were sig nificantly delayed when it matched the color of the object to which participants were asked to saccade (Boot & Brockmole, 2010). The result of this study and replications suggest an automatic delay in disengagement away from items consistent with an observer's goals (Blakely et al, 2012;Wright et ah, in press). Of interest to the authors, bottom up salience of the fixated but irrelevant item was found not to influence disengagement times (Brockmole & Boot, 2009;see Bom, Kerzel, & Theeuwes, 2011, for similar findings).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Compared with when the center object was any other color, saccades away from the center object were sig nificantly delayed when it matched the color of the object to which participants were asked to saccade (Boot & Brockmole, 2010). The result of this study and replications suggest an automatic delay in disengagement away from items consistent with an observer's goals (Blakely et al, 2012;Wright et ah, in press). Of interest to the authors, bottom up salience of the fixated but irrelevant item was found not to influence disengagement times (Brockmole & Boot, 2009;see Bom, Kerzel, & Theeuwes, 2011, for similar findings).…”
mentioning
confidence: 56%
“…From these calculations, positive values indicate slower disengagement when the center item was green, and negative values suggest slower disengagement when the center item was blue (see Blakely et al, 2012 for similar calculations of disengage ment effects). SRT difference scores were entered into an analysis of variance with target color (green or blue) as a between-subjects factor.…”
Section: Replication Of Boot and Brockmole (2010)mentioning
confidence: 99%
“…In the contingent capture paradigm, a color singleton only captures attention when participants are searching for a color singleton target, and an onset cue will only capture attention when participants are searching for an onset target. Theeuwes (2010) argued that both onset and color singleton cues capture attention regardless of the observer's goal, but attention will only linger at the cue location when the cue matches the observer's attention set (see Blakely, Wright, Dehili, Boot, & Brockmole, 2012;Boot & Brockmole, 2010, for similar effects). Color singleton cues will capture attention even when participants are searching for onset targets, but attention will quickly be disengaged because the capturing stimulus is dissimilar from the target.…”
mentioning
confidence: 99%
“…Self-esteem is considered as the product of intuitive, automatic process of affective experiences which is somehow influenced by social interactions. While explicit self-esteem is achieved through conscious and rational processing of self-relevant information (Blakely et al, 2012). The implicit self-esteem can be altered but not the explicit (Foley, 2004).…”
Section: Self-esteemmentioning
confidence: 99%
“…Customer disengagement is still an unexplored area. A handsome work is done in the area of moral disengagement (Aquino et al, 2007); somewhat in employee disengagement (Pech & Slade, 2006); attentional disengagement (Blakely et al, 2012), and academic disengagement (Foley, 2004). Table one is given to display the definitions of disengagement in other areas of studies.…”
Section: Introductionmentioning
confidence: 99%